Schwannoma of the base of the tongue mimicking fibroma - Sukhvinder Singh Rana; Neera Ohri (Wolters Kluwer Medknow Publications, 2018)
Schwannoma is a slow-growing benign tumor of the nerve sheath. It originates from the Schwann cell of the peripheral, autonomic, and cranial nerve. It is usually a single, circumscribed, firm, painless lesion of variable size. 25%-40% of all schwannomas are considered to affect the head and neck region, with the parapharyngeal space being the most common location. Only 1% of cases are intraoral. The treatment of choice is surgical excision of the tumor. Schwannomas do not show recurrence if completely excised. We report a case of schwannoma of the base of the tongue mimicking fibroma.